Texas Water Journal 2019
DOI: 10.21423/twj.v10i1.7062
|View full text |Cite
|
Sign up to set email alerts
|

Interjecting Economics into the Surface Water Dialogue

Abstract: This paper applies the conceptual lens of economic efficiency as a criterion by which to evaluate surface water in Texas. We identify two major problems. First, Texas has a water allocation problem limiting the ability to substitute groundwater for surface water to move water between river basins and to facilitate transfers within a river basin. Second, surface water is both underpriced and unresponsive to drought conditions preventing it from being used at its highest and best use. We propose a variety of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Also, focused flows could be secured through market-based approaches (i.e., purchasing permanent rights, spot market transactions, or options contracts) because smaller volumes of water are more likely to be available than larger volumes. It has been suggested that a water market in Texas could encourage water conservation (Vaca et al 2019). Focused flows from water transactions could also be created by mitigation or restoration actions, or a permanent water right.…”
Section: One Potential Solution: Focused Flowsmentioning
confidence: 99%
“…Also, focused flows could be secured through market-based approaches (i.e., purchasing permanent rights, spot market transactions, or options contracts) because smaller volumes of water are more likely to be available than larger volumes. It has been suggested that a water market in Texas could encourage water conservation (Vaca et al 2019). Focused flows from water transactions could also be created by mitigation or restoration actions, or a permanent water right.…”
Section: One Potential Solution: Focused Flowsmentioning
confidence: 99%